A aquisição de língua materna e não materna Questões gerais e dados do Português - Lúcia Santos, Ana; João Freitas, Maria (Textbooks in Language Sciences, 2017)
The present volume is an introduction to the study of Language Acquisition, especially centered on Portuguese. Even though the different chapters always take Portuguese as a point of departure, a comparative perspective is assumed and Portuguese data is compared to data from other languages, when relevant. This book aims at filling a gap in the literature: an introductory textbook to be used by students of Language Acquisition in Portuguese-speaking countries. The book is composed by chapters authored by several Portuguese and Brazilian researchers and it presents in textbook format a relevant part of the research results obtained during the last decades. The book starts with a general historical presentation of the field. The following chapters explore the acquisition of phonology and syntax and consider the problem of typical and atypical development, as well as linguistic assessment. Bilingualism and L2 acquisition are the topics of two independent chapters. Two final chapters discuss the development of linguistic awareness, in relation to the acquisition of writing.